PENGEMBANGAN MEDIA DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR BAHASA ARAB DI KELAS VII MTSN YOGYAKARTA I - Dini Latifah (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2016)
This study aims to determine the effectiveness of diorama media and whether there is a significant difference in improving the learning outcomes of Arabic language in terms of the reading skills of class VII students of MTsN Yogakarta I. The test of the instrument using the validity and reliability test showed that 25 test questions all proved valid and reliable with a reliability coefficient of 0.957 for multiple choice and 0.978 for essay. Before the data were analyzed, the data should be tested by kolmogorov smirnov test and Varian analysis test (ANOVA) to know that the data were normally distributed and homogeneous. Furthermore, the data were tested with